2020
DOI: 10.1038/s41388-020-1246-z
|View full text |Cite
|
Sign up to set email alerts
|

Tumor progression and chromatin landscape of lung cancer are regulated by the lineage factor GATA6

Abstract: Lineage selective transcription factors (TFs) are important regulators of tumorigenesis, but their biological functions are often context dependent with undefined epigenetic mechanisms of action. In this study, we uncover a conditional role for the endodermal and pulmonary specifying TF GATA6 in lung adenocarcinoma (LUAD) progression. Impairing Gata6 in genetically engineered mouse models reduces the proliferation and increases the differentiation of Kras mutant LUAD tumors. These effects are influenced by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…Integration of phylodynamics and transcriptome uncovers fitness-associated gene programs for KP tumors With quantitative measurements of single-cell fitness in each tumor, we next sought to identify the molecular features consistently associated with subclonal expansions. Consistent with KP tumor progression being driven largely by epigenetic rather than genetic changes (LaFave et al, 2020;Arnal-Estape ´et al, 2020;Marjanovic et al, 2020), we observed that CNV profiles within expansions were largely inconsistent across tumors (Figure S2L). We therefore examined the transcriptomic differences underpinning expansion.…”
Section: Ll Open Accesssupporting
confidence: 68%
“…Integration of phylodynamics and transcriptome uncovers fitness-associated gene programs for KP tumors With quantitative measurements of single-cell fitness in each tumor, we next sought to identify the molecular features consistently associated with subclonal expansions. Consistent with KP tumor progression being driven largely by epigenetic rather than genetic changes (LaFave et al, 2020;Arnal-Estape ´et al, 2020;Marjanovic et al, 2020), we observed that CNV profiles within expansions were largely inconsistent across tumors (Figure S2L). We therefore examined the transcriptomic differences underpinning expansion.…”
Section: Ll Open Accesssupporting
confidence: 68%
“…revealed that silencing of GATA6 exerts anti-oncogenic effects in LUAD [ 46 ]. Inhibition of GATA6 reduces the proliferation of Kras mutant LUAD tumors in mouse models [ 47 ]. GATA6 activates PCAT1 to maintain stemness of non-small cell lung cancer cells [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…With quantitative measurements of single-cell fitness in each tumor, we next sought to identify the molecular features consistently associated with subclonal expansions. Consistent with KP tumors having low mutational burden and progression mainly utilizing epigenetic changes as major drivers (Arnal-Estapé et al, 2020;LaFave et al, 2020), CNV profiles within expansions were largely inconsistent across tumors and thus unlikely to be the only driver of tumor expansion (Fig S2L). We therefore examined the transcriptomic differences underpinning expansion.…”
Section: Integration Of Phylodynamics and Transcriptome Uncovers Fitness-associated Gene Programs For Kp Tumorsmentioning
confidence: 58%